The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1101/389494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A validation of the diathesis-stress model for depression in Generation Scotland

Abstract: Depression has well-established influences from genetic and environmental risk factors. This has led to the diathesis-stress theory, which assumes a multiplicative gene-by-environment interaction (GxE) effect on risk. Recently, Colodro-Conde et al. empirically tested this theory, using the polygenic risk score for major depressive disorder (PRS, genes) and stressful life events (SLE, environment) effects on depressive symptoms, identifying significant GxE effects with an additive contribution to liability. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…To more comprehensively capture genome-by-trauma interactions within depression and neuroticism, the approach uses all genotyped variants to compute genetic similarity instead of individual SNVs or PGSs as in some previous studies. 16,19,27 We computed trauma exposure and genome-by-trauma interaction similarity to explore trait variance attributable to these effects by incorporating the genetic, trauma exposure, and interaction terms as random e f f e c t s a s o p p o s e d t o f i xe d e f f e c t s w it h i n l i n e a r models. 19,20,27 Moreover, we used all related individuals, with appropriate sensitivity analyses (limited to unrelated individuals only).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To more comprehensively capture genome-by-trauma interactions within depression and neuroticism, the approach uses all genotyped variants to compute genetic similarity instead of individual SNVs or PGSs as in some previous studies. 16,19,27 We computed trauma exposure and genome-by-trauma interaction similarity to explore trait variance attributable to these effects by incorporating the genetic, trauma exposure, and interaction terms as random e f f e c t s a s o p p o s e d t o f i xe d e f f e c t s w it h i n l i n e a r models. 19,20,27 Moreover, we used all related individuals, with appropriate sensitivity analyses (limited to unrelated individuals only).…”
Section: Discussionmentioning
confidence: 99%
“…16,[19][20][21][22] Moreover, research using polygenic scores (PGSs)genetic measures that can be calculated for each individual by identifying, weighting, and summing genotyped risk variants found to be associated with depression 23,24 -have yielded inconsistent findings. Some studies have highlighted sex differences 25 and found significant interaction associations with MDD outcomes, 16,18,[25][26][27] whereas some replication attempts reported null findings. [28][29][30] An explanation for inconsistent findings may lie in the predictive accuracy and validity of PGSs.…”
mentioning
confidence: 99%
“…Interaction between polygenic risk of MDD and recent SLE are reported to increase liability to depressive symptoms 4,16 ; validating the implementation of genome-wide approaches to study GxE in depression. Most GxE studies for MDD have been conducted on candidate genes, or using polygenic approaches to a wide range of environmental risk factors, with some contradictory findings 28-32 .…”
Section: Introductionmentioning
confidence: 86%
“…There is strong evidence for the role of stressful life events (SLE) as risk factor and trigger for depression 8-12 . Genetic control of sensitivity to stress may vary between individuals, resulting in individual differences in the depressogenic effects of SLE, i.e., genotype-by-environment interaction (GxE) 4,13-16 . Significant evidence of GxE has been reported for common respiratory diseases and some forms of cancer 17-22 , and GxE studies have identified genetic risk variants not found by genome-wide association studies (GWAS) 23-27 .…”
Section: Introductionmentioning
confidence: 99%
“…Replication of gene-trait associations identified in GWAS and their functional analyses continues to be critical. GWEIS (genome-wide by environment interaction study) brings G-E interaction analyses into GWAS, but GWEISs are uncommon (23). One challenge is to develop models that will enable multilayered measurements within environments to be incorporated into GWEIS designs.…”
Section: Gene-environment Interplaymentioning
confidence: 99%